Thermal Modeling of Blade Lithium Iron Phosphate Battery with Liquid Cooling and Addition of Manganese to Cathode - Nurul Widyasari; Bambang Priyono (Lamintang Education and Training (LET) Centre, 2025)
Electric vehicles are a key alternative to fossil fuel-based transportation but face challenges in safety and driving range. Blade battery technology, with its long and flat shape, offers improved heat distribution and safety. This study focuses on the thermal performance of a blade-shaped Lithium Iron Phosphate (LFP) battery enhanced with manganese (LMFP), using a water-based cooling system to ensure temperature stability during operation. Effective thermal management, including the use of cooling systems, is crucial for maintaining battery performance and reliability. This study modeled a blade-shaped battery with a water-cooling system using ANSYS Fluent. The process involves designing 3D geometry and meshing to simulate thermal behavior accurately. The simulation was conducted under varying operating conditions by applying different inlet temperatures for the cooling system (14.85°C, 26.85°C, and 34.85°C ) combined with different discharge rates (0.5C, 1C, 2C, and 5C). These parameter variations were designed to evaluate the thermal response of the battery under realistic and dynamic working environments. The results indicate that the cooling system can maintain the battery temperature within the optimal thermal range, with the maximum temperature remaining below 35°C across all tested conditions. Higher C-rates resulted in increased internal heat generation, leading to higher cell temperatures. This study contributes to the development of thermally stable, higher-energy-density batteries, offering practical insights for designing safer and more efficient battery packs in electric vehicles.